Electronic transport layer with gradient porosity, preparation method thereof and perovskite solar cell

CN122935110APending Publication Date: 2026-10-16HUANENG CLEAN ENERGY RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610805361.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,若三维纳米层颗粒表面不平整或者晶格不匹配,将导致一维纳米线/纳米棒阵列倾斜、缠绕或者穿透三维层从基底直接生长,最后导致结构分层失败,无法形成具有梯度孔隙率的电子传输层

Benefits of technology

本发明中薄层的致密TiO2阻挡层使得三维介孔层表面平整,且晶格匹配,确保了一维纳米棒的垂直取向,避免了导电基底与钙钛矿前驱体溶液直接接触导致的短路;三维介孔层为小孔径高比表面网络,一维纳米棒层为较大间距的垂直通道,垂直通道为溶液提供快速渗透路径,三维层提供毛细吸附力,实现钙钛矿前驱体溶液的快速充分浸润;三维层的曲折表面大幅增加电子提取接触点,使得界面接触面积增大;光生电子可沿纳米棒直接到达基底,避免了传统介孔层中的多次跳跃与复合,从而提高了器件的光电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935110A_ABST
    Figure CN122935110A_ABST
Patent Text Reader

Abstract

The application discloses an electron transport layer with gradient porosity, a preparation method thereof and a perovskite solar cell. In the application, a three-dimensional mesoporous layer and a one-dimensional nanorod layer form gradient porosity, a dense TiO2 blocking layer of a thin layer makes the surface of the three-dimensional mesoporous layer smooth and lattice-matched, ensures vertical orientation of the one-dimensional nanorod, and avoids short circuit caused by direct contact of a conductive substrate with a perovskite precursor solution; the three-dimensional mesoporous layer is a small-aperture high-specific-surface network, and the one-dimensional nanorod layer is a vertical channel with a larger spacing, the vertical channel provides a rapid penetration path for a solution, the three-dimensional layer provides capillary adsorption force, and rapid and sufficient infiltration of the perovskite precursor solution is realized; the tortuous surface of the three-dimensional layer greatly increases electron extraction contact points, so that the interface contact area is increased; photo-generated electrons can directly reach the substrate along the nanorod, multiple jumps and recombination in a traditional mesoporous layer are avoided, and therefore the photoelectric performance of the device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, and more particularly to an electron transport layer with gradient porosity, a method for preparing the same, and a perovskite solar cell. Background Technology

[0002] In perovskite solar cells, the microstructure of the electron transport layer is a crucial factor affecting the device's photoelectric performance. One-dimensional nanowire / nanorobar arrays are highly oriented along their length, while three-dimensional nanolayer particles possess a high specific surface area. Combining three-dimensional nanolayer particles with one-dimensional nanowire / nanorobar arrays involves first depositing a layer of three-dimensional nanolayer particles with a high specific surface area, and then fabricating a vertically oriented one-dimensional nanowire / nanorobar array. This allows the perovskite precursor solution to fully wet and fill the pores, forming a continuous heterojunction interface and providing a straight, fast transport channel for photogenerated electrons, significantly reducing grain boundary scattering and recombination losses. However, if the surface of the three-dimensional nanolayer particles is uneven or the lattice is mismatched, the one-dimensional nanowire / nanorobar array will tilt, become entangled, or grow directly from the substrate through the three-dimensional layer, ultimately leading to structural delamination failure and the inability to form an electron transport layer with gradient porosity. Summary of the Invention

[0003] The present invention aims to at least partially solve one of the technical problems in the related art.

[0004] Therefore, embodiments of the present invention propose an electron transport layer with gradient porosity, a method for its fabrication, and a perovskite solar cell.

[0005] In a first aspect, the present invention proposes a method for preparing an electron transport layer with gradient porosity, comprising the following steps:

[0006] (1) Tetrabutyl titanate solution was spin-coated onto a pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer; (2) Spin-coating the mesoporous TiO2 nanoparticle dispersion onto the dense TiO2 barrier layer and sintering to obtain a three-dimensional mesoporous layer; (3) The conductive substrate obtained in step (2) is placed in an acidic solution of tetrabutyl titanate and subjected to a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on the three-dimensional mesoporous layer. (4) After taking out the conductive substrate obtained in step (3), rinse and sinter it to obtain an electron transport layer with gradient porosity.

[0007] Furthermore, the concentration of the tetrabutyl titanate solution is 0.2~0.4M.

[0008] Furthermore, in step (1), the spin coating speed is 3000~4000 rpm and the spin coating time is 30~50s.

[0009] Furthermore, in step (1), the sintering temperature is 450~500℃ and the sintering time is 20~40min.

[0010] Furthermore, the thickness of the dense TiO2 barrier layer is 30~50nm.

[0011] Furthermore, the thickness of the three-dimensional mesoporous layer is 100~200nm.

[0012] Furthermore, the mesoporous TiO2 nanoparticle dispersion is obtained by homogenizing mesoporous TiO2 nanoparticles in ethanol or terpineol.

[0013] Furthermore, the one-dimensional TiO2 nanorod array has nanorods with a diameter of 30-50 nm, a spacing of 90-120 nm, and a length of 400-700 nm.

[0014] Furthermore, the acidic solution of tetrabutyl titanate is obtained by first mixing hydrochloric acid and water evenly, and then adding tetrabutyl titanate dropwise and stirring until clear and transparent.

[0015] Furthermore, the hydrothermal reaction is carried out at a temperature of 150-170°C for a duration of 4-12 hours.

[0016] Secondly, the present invention provides an electron transport layer with gradient porosity prepared by the method proposed in the first aspect above.

[0017] Thirdly, the present invention proposes a perovskite solar cell, wherein the perovskite solar cell comprises an electron transport layer with gradient porosity prepared by the method proposed in the first aspect above, or an electron transport layer with gradient porosity proposed in the second aspect above.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: In this invention, the thin, dense TiO2 barrier layer ensures a smooth surface and lattice matching of the three-dimensional mesoporous layer, guaranteeing the vertical orientation of the one-dimensional nanorods and preventing short circuits caused by direct contact between the conductive substrate and the perovskite precursor solution. The three-dimensional mesoporous layer is a small-pore, high-specific-surface-area network, while the one-dimensional nanorod layer provides vertically spaced channels. These vertical channels offer a rapid penetration path for the solution, and the three-dimensional layer provides capillary adsorption, enabling rapid and thorough wetting of the perovskite precursor solution. The tortuous surface of the three-dimensional layer significantly increases the number of electron extraction contact points, resulting in a larger interfacial contact area. Photogenerated electrons can directly reach the substrate along the nanorods, avoiding multiple jumps and recombinations as in traditional mesoporous layers, thereby improving the optoelectronic performance of the device. Attached Figure Description

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings, wherein: Figure 1 This is a flowchart of the method for preparing an electron transport layer with gradient porosity according to the present invention. Detailed Implementation

[0020] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0021] The following description, in conjunction with the accompanying drawings, describes the electron transport layer with gradient porosity proposed in this invention, its preparation method, and a perovskite solar cell.

[0022] like Figure 1 As shown, the method for preparing an electron transport layer with gradient porosity according to the present invention includes the following steps: (1) Tetrabutyl titanate solution was spin-coated onto a pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer; (2) Spin-coating the mesoporous TiO2 nanoparticle dispersion onto a dense TiO2 barrier layer and sintering to obtain a three-dimensional mesoporous layer; (3) The conductive substrate obtained in step (2) is placed in an acidic solution of tetrabutyl titanate and subjected to a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer. (4) After taking out the conductive substrate obtained in step (3), rinse and sinter it to obtain an electron transport layer with gradient porosity.

[0023] Step (1) is the preparation process of a dense TiO2 barrier layer. The conductive substrate is ITO or FTO. First, the conductive substrate is ultrasonically cleaned with detergent, deionized water, acetone and ethanol for 15-20 min respectively. Then, it is dried with nitrogen and treated under ultraviolet-ozone conditions for 15-20 min to remove organic residues and improve surface wettability.

[0024] A tetrabutyl titanate solution was spin-coated onto a pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer. The tetrabutyl titanate solution was obtained by dissolving tetrabutyl titanate in ethanol solvent, and the concentration of the tetrabutyl titanate solution was 0.2~0.4M.

[0025] In some embodiments, in step (1), the spin coating speed is 3000~4000 rpm, the spin coating time is 30~50s, the sintering temperature is 450~500℃, and the sintering time is 20~40min.

[0026] In some embodiments, the thickness of the dense TiO2 barrier layer is 30-50 nm. The dense TiO2 barrier layer is used to prevent short circuits caused by direct contact between the conductive substrate and the perovskite.

[0027] Step (2) is the preparation process of the three-dimensional mesoporous layer. The mesoporous TiO2 nanoparticle dispersion is spin-coated onto the dense TiO2 barrier layer and sintered to obtain the three-dimensional mesoporous layer.

[0028] The mesoporous TiO2 nanoparticle dispersion was obtained by dispersing mesoporous TiO2 nanoparticles in ethanol or terpineol and homogenizing them. The homogenization speed was 1000~1200 rpm and the homogenization time was 20~50 s. The particle size of the mesoporous TiO2 nanoparticles was 20~50 nm.

[0029] In some embodiments, the sintering temperature is 450~500℃ and the sintering time is 30~40min. It is understood that the temperature is allowed to cool naturally to room temperature after sintering before proceeding to the next step to avoid thermal stress affecting the subsequent growth of nanorods.

[0030] In some embodiments, the thickness of the three-dimensional mesoporous layer is 100-200 nm. The three-dimensional mesoporous layer is a small-pore, high-specific-surface-area network used to increase the specific surface area and ensure sufficient wetting and interfacial contact of the perovskite precursor solution.

[0031] Step (3) is the preparation process of a one-dimensional TiO2 nanorod array. The conductive substrate obtained in step (2) is placed in an acidic solution of tetrabutyl titanate with the conductive surface facing down and tilted against the wall. A hydrothermal reaction is carried out to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer.

[0032] The acidic solution of tetrabutyl titanate was obtained by first mixing hydrochloric acid and water thoroughly, then adding tetrabutyl titanate dropwise and stirring until clear and transparent. Hydrochloric acid was used to inhibit the excessively rapid hydrolysis of the titanium source, thereby controlling the crystal orientation. The hydrothermal reaction temperature was 150–170℃, and the reaction time was 4–12 h. The hydrothermal reaction temperature needed to be within a suitable range to obtain a uniform nanorod array. When the temperature was below 150℃, the growth rate was slow, and when the temperature was above 180℃, secondary nucleation was likely to occur.

[0033] In some embodiments, the one-dimensional TiO2 nanorod array has a nanorod diameter of 30-50 nm, a spacing of 90-120 nm, and a length of 400-700 nm. The one-dimensional TiO2 nanorod array is a vertical channel with a relatively large spacing. The spacing needs to be controlled within a suitable range. If the spacing is too small, the expansion of perovskite crystals may squeeze or break the nanorods; if the spacing is too large, the advantage of a fast channel will be lost.

[0034] Step (4) is the post-processing process. After the hydrothermal reaction is completed, the substrate is naturally cooled to room temperature. The conductive substrate is then removed and rinsed three times with deionized water and ethanol alternately. Finally, it is sintered at 450°C for 30-40 minutes to remove residual organic matter and improve crystallinity.

[0035] This invention first prepares a thin, dense TiO2 barrier layer on a conductive substrate, then prepares a three-dimensional mesoporous layer on top of it, and finally prepares a one-dimensional TiO2 nanorod array on the three-dimensional mesoporous layer. The three-dimensional mesoporous layer and the one-dimensional nanorod layer form a gradient porosity. The thin, dense TiO2 barrier layer ensures a smooth surface and lattice matching of the three-dimensional mesoporous layer, guaranteeing the vertical orientation of the one-dimensional nanorods and avoiding short circuits caused by direct contact between the conductive substrate and the perovskite precursor solution. The three-dimensional mesoporous layer is a small-pore, high-specific-surface-area network, while the one-dimensional nanorod layer provides vertically spaced channels. These vertical channels provide a rapid permeation path for the solution, and the three-dimensional layer provides capillary adsorption, enabling rapid and thorough wetting of the perovskite precursor solution. The tortuous surface of the three-dimensional layer significantly increases the electron extraction contact points, resulting in a larger interfacial contact area. Photogenerated electrons can directly reach the substrate along the nanorods, avoiding multiple jumps and recombinations as in traditional mesoporous layers, thereby improving the photoelectric performance of the device.

[0036] The electron transport layer of the present invention is prepared by the method of the present invention, and the perovskite solar cell of the present invention includes the electron transport layer of the present invention.

[0037] The present invention will now be described in detail with reference to specific embodiments.

[0038] Example 1 (1) The FTO conductive substrate (2.5cm×2.5cm) was ultrasonicated for 15min each with detergent, deionized water, acetone and ethanol, dried with nitrogen, and then treated with ultraviolet-ozone for 15min and cooled to room temperature for use.

[0039] (2) Tetrabutyl titanate ethanol solution was spin-coated onto the pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer. The concentration of tetrabutyl titanate solution was 0.3M, the spin-coating speed was 3500rpm, the spin-coating time was 40s, the sintering temperature was 500℃, the sintering time was 30min, and the thickness of the dense TiO2 barrier layer was 40nm.

[0040] (3) Mesoporous TiO2 nanoparticles were dispersed in ethanol and homogenized to obtain a mesoporous TiO2 nanoparticle dispersion. The homogenization speed was 1000 rpm and the homogenization time was 30 s. The mesoporous TiO2 nanoparticle dispersion was spin-coated onto a dense TiO2 barrier layer and sintered to obtain a three-dimensional mesoporous layer. The sintering temperature was 500℃ and the sintering time was 30 min. The thickness of the three-dimensional mesoporous layer was 150 nm.

[0041] (4) Deionized water and concentrated hydrochloric acid (36-38 wt%) were mixed in a volume ratio of 1:1, and then tetrabutyl titanate was slowly added dropwise and stirred until clear and transparent to obtain an acidic solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to concentrated hydrochloric acid was 1:30. Then, the conductive substrate was placed in the acidic solution of tetrabutyl titanate with the conductive surface facing down and tilted against the wall to carry out a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer. The hydrothermal reaction temperature was 170℃ and the time was 5h. The diameter of the one-dimensional TiO2 nanorod array was 35nm, the spacing was 100nm, and the length was 450nm. After the hydrothermal reaction was completed, the substrate was naturally cooled to room temperature, the conductive substrate was taken out, and it was rinsed three times alternately with deionized water and ethanol. Then, it was sintered at 450℃ for 30min to obtain an electron transport layer.

[0042] (5) Dissolve 600 mg PbI2 and 6 mg MAI in 5 ml of a mixed solvent of DMF and DMSO with a volume ratio of 4:1, and stir until dissolved to obtain a PbI2 precursor solution. Spin-coat the PbI2 precursor solution onto the electron transport layer and anneal to obtain a perovskite light-absorbing layer with a thickness of 600 nm. The spin-coating time is 30 s, the spin-coating speed is 4000 rpm, the annealing temperature is 140 °C, and the annealing time is 25 min.

[0043] (6) Dissolve 65 mg Spiro-OMeTAD in 1 ml of chlorobenzene, mix well, and then spin-coat 60 μL onto the perovskite light-absorbing layer to obtain the hole transport layer.

[0044] (7) In 10 -4 Under vacuum conditions, an Ag electrode with a thickness of 110 nm was deposited on the hole transport layer by thermal evaporation to obtain a perovskite solar cell.

[0045] Example 2 (1) The FTO conductive substrate (2.5cm×2.5cm) was ultrasonicated for 15min each with detergent, deionized water, acetone and ethanol, dried with nitrogen, and then treated with ultraviolet-ozone for 15min and cooled to room temperature for use.

[0046] (2) Tetrabutyl titanate ethanol solution was spin-coated onto the pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer. The concentration of tetrabutyl titanate solution was 0.4M, the spin-coating speed was 3500rpm, the spin-coating time was 40s, the sintering temperature was 500℃, the sintering time was 30min, and the thickness of the dense TiO2 barrier layer was 30nm.

[0047] (3) Mesoporous TiO2 nanoparticles were dispersed in ethanol and homogenized to obtain a mesoporous TiO2 nanoparticle dispersion. The homogenization speed was 1000 rpm and the homogenization time was 30 s. The mesoporous TiO2 nanoparticle dispersion was spin-coated onto a dense TiO2 barrier layer and sintered to obtain a three-dimensional mesoporous layer. The sintering temperature was 500℃ and the sintering time was 30 min. The thickness of the three-dimensional mesoporous layer was 100 nm.

[0048] (4) Deionized water and concentrated hydrochloric acid (36-38 wt%) were mixed in a volume ratio of 1:1, and then tetrabutyl titanate was slowly added dropwise and stirred until clear and transparent to obtain an acidic solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to concentrated hydrochloric acid was 1:30. Then, the conductive substrate was placed in the acidic solution of tetrabutyl titanate with the conductive surface facing down and tilted against the wall to carry out a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer. The hydrothermal reaction temperature was 170℃ and the time was 9h. The diameter of the one-dimensional TiO2 nanorod array was 40nm, the spacing was 100nm, and the length was 540nm. After the hydrothermal reaction was completed, the substrate was naturally cooled to room temperature, the conductive substrate was taken out, and it was rinsed three times alternately with deionized water and ethanol. Then, it was sintered at 450℃ for 30min to obtain an electron transport layer.

[0049] (5) Dissolve 600 mg PbI2 and 6 mg MAI in 5 ml of a mixed solvent of DMF and DMSO with a volume ratio of 4:1, and stir until dissolved to obtain a PbI2 precursor solution. Spin-coat the PbI2 precursor solution onto the electron transport layer and anneal to obtain a perovskite light-absorbing layer with a thickness of 600 nm. The spin-coating time is 30 s, the spin-coating speed is 4000 rpm, the annealing temperature is 140 °C, and the annealing time is 25 min.

[0050] (6) Dissolve 65 mg Spiro-OMeTAD in 1 ml of chlorobenzene, mix well, and then spin-coat 60 μL onto the perovskite light-absorbing layer to obtain the hole transport layer.

[0051] (7) In 10 -4 Under vacuum conditions, an Ag electrode with a thickness of 110 nm was deposited on the hole transport layer by thermal evaporation to obtain a perovskite solar cell.

[0052] Example 3 (1) The FTO conductive substrate (2.5cm×2.5cm) was ultrasonicated for 15min each with detergent, deionized water, acetone and ethanol, dried with nitrogen, and then treated with ultraviolet-ozone for 15min and cooled to room temperature for use.

[0053] (2) Tetrabutyl titanate ethanol solution was spin-coated onto the pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer. The concentration of tetrabutyl titanate solution was 0.2M, the spin-coating speed was 3500rpm, the spin-coating time was 40s, the sintering temperature was 500℃, the sintering time was 30min, and the thickness of the dense TiO2 barrier layer was 50nm.

[0054] (3) Mesoporous TiO2 nanoparticles were dispersed in ethanol and homogenized to obtain a mesoporous TiO2 nanoparticle dispersion. The homogenization speed was 1000 rpm and the homogenization time was 30 s. The mesoporous TiO2 nanoparticle dispersion was spin-coated onto a dense TiO2 barrier layer and sintered to obtain a three-dimensional mesoporous layer. The sintering temperature was 500℃ and the sintering time was 30 min. The thickness of the three-dimensional mesoporous layer was 200 nm.

[0055] (4) Deionized water and concentrated hydrochloric acid (36-38 wt%) were mixed in a volume ratio of 1:1, and then tetrabutyl titanate was slowly added dropwise and stirred until clear and transparent to obtain an acidic solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to concentrated hydrochloric acid was 1:30. Then, the conductive substrate was placed in the acidic solution of tetrabutyl titanate with the conductive surface facing down and tilted against the wall to carry out a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer. The hydrothermal reaction temperature was 170℃ and the time was 12h. The diameter of the one-dimensional TiO2 nanorod array was 47nm, the spacing was 100nm, and the length was 650nm. After the hydrothermal reaction was completed, the substrate was naturally cooled to room temperature, the conductive substrate was taken out, and it was rinsed three times alternately with deionized water and ethanol. Then, it was sintered at 450℃ for 30min to obtain an electron transport layer.

[0056] (5) Dissolve 600 mg PbI2 and 6 mg MAI in 5 ml of a mixed solvent of DMF and DMSO with a volume ratio of 4:1, and stir until dissolved to obtain a PbI2 precursor solution. Spin-coat the PbI2 precursor solution onto the electron transport layer and anneal to obtain a perovskite light-absorbing layer with a thickness of 600 nm. The spin-coating time is 30 s, the spin-coating speed is 4000 rpm, the annealing temperature is 140 °C, and the annealing time is 25 min.

[0057] (6) Dissolve 65 mg Spiro-OMeTAD in 1 ml of chlorobenzene, mix well, and then spin-coat 60 μL onto the perovskite light-absorbing layer to obtain the hole transport layer.

[0058] (7) In 10 -4 Under vacuum conditions, an Ag electrode with a thickness of 110 nm was deposited on the hole transport layer by thermal evaporation to obtain a perovskite solar cell.

[0059] Comparative Example 1 (1) The FTO conductive substrate (2.5cm×2.5cm) was ultrasonicated for 15min each with detergent, deionized water, acetone and ethanol, dried with nitrogen, and then treated with ultraviolet-ozone for 15min and cooled to room temperature for use.

[0060] (2) Mesoporous TiO2 nanoparticles were dispersed in ethanol and homogenized to obtain a mesoporous TiO2 nanoparticle dispersion. The homogenization speed was 1000 rpm and the homogenization time was 30 s. The mesoporous TiO2 nanoparticle dispersion was spin-coated onto a conductive substrate and sintered to obtain a three-dimensional mesoporous layer. The sintering temperature was 500℃ and the sintering time was 30 min. The thickness of the three-dimensional mesoporous layer was 150 nm.

[0061] (3) Deionized water and concentrated hydrochloric acid (36-38 wt%) were mixed in a volume ratio of 1:1, and then tetrabutyl titanate was slowly added dropwise and stirred until clear and transparent to obtain an acidic solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to concentrated hydrochloric acid was 1:30. Then, the conductive substrate was placed in the acidic solution of tetrabutyl titanate with the conductive surface facing down and tilted against the wall to carry out a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer. The hydrothermal reaction temperature was 170℃ and the time was 5h. The diameter of the one-dimensional TiO2 nanorod array was 35nm, the spacing was 100nm, and the length was 450nm. After the hydrothermal reaction was completed, the substrate was naturally cooled to room temperature, the conductive substrate was taken out, and it was rinsed three times alternately with deionized water and ethanol. Then, it was sintered at 450℃ for 30min to obtain an electron transport layer.

[0062] (4) Dissolve 600 mg PbI2 and 6 mg MAI in 5 ml of a mixed solvent of DMF and DMSO with a volume ratio of 4:1, and stir until dissolved to obtain a PbI2 precursor solution. Spin-coat the PbI2 precursor solution onto the electron transport layer and anneal to obtain a perovskite light-absorbing layer with a thickness of 600 nm. The spin-coating time is 30 s, the spin-coating speed is 4000 rpm, the annealing temperature is 140 °C, and the annealing time is 25 min.

[0063] (5) Dissolve 65 mg Spiro-OMeTAD in 1 ml of chlorobenzene, mix well, and then spin-coat 60 μL onto the perovskite light-absorbing layer to obtain the hole transport layer.

[0064] (6) In 10 -4 Under vacuum conditions, an Ag electrode with a thickness of 110 nm was deposited on the hole transport layer by thermal evaporation to obtain a perovskite solar cell.

[0065] Comparative Example 2 (1) The FTO conductive substrate (2.5cm×2.5cm) was ultrasonicated for 15min each with detergent, deionized water, acetone and ethanol, dried with nitrogen, and then treated with ultraviolet-ozone for 15min and cooled to room temperature for use.

[0066] (2) Mesoporous TiO2 nanoparticles were dispersed in ethanol and homogenized to obtain a mesoporous TiO2 nanoparticle dispersion. The homogenization speed was 1000 rpm and the homogenization time was 30 s. The mesoporous TiO2 nanoparticle dispersion was spin-coated onto a dense TiO2 barrier layer and sintered to obtain a three-dimensional mesoporous layer. The sintering temperature was 500℃ and the sintering time was 30 min. The thickness of the three-dimensional mesoporous layer was 100 nm.

[0067] (3) Deionized water and concentrated hydrochloric acid (36-38 wt%) were mixed in a volume ratio of 1:1, and then tetrabutyl titanate was slowly added dropwise and stirred until clear and transparent to obtain an acidic solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to concentrated hydrochloric acid was 1:30. Then, the conductive substrate was placed in the acidic solution of tetrabutyl titanate with the conductive surface facing down and tilted against the wall to carry out a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on a three-dimensional mesoporous layer. The hydrothermal reaction temperature was 170℃ and the time was 9h. The diameter of the one-dimensional TiO2 nanorod array was 40nm, the spacing was 100nm, and the length was 540nm. After the hydrothermal reaction was completed, the substrate was naturally cooled to room temperature, the conductive substrate was taken out, and it was rinsed three times alternately with deionized water and ethanol. Then, it was sintered at 450℃ for 30min to obtain an electron transport layer.

[0068] (4) Dissolve 600 mg PbI2 and 6 mg MAI in 5 ml of a mixed solvent of DMF and DMSO with a volume ratio of 4:1, and stir until dissolved to obtain a PbI2 precursor solution. Spin-coat the PbI2 precursor solution onto the electron transport layer and anneal to obtain a perovskite light-absorbing layer with a thickness of 600 nm. The spin-coating time is 30 s, the spin-coating speed is 4000 rpm, the annealing temperature is 140 °C, and the annealing time is 25 min.

[0069] (5) Dissolve 65 mg Spiro-OMeTAD in 1 ml of chlorobenzene, mix well, and then spin-coat 60 μL onto the perovskite light-absorbing layer to obtain the hole transport layer.

[0070] (6) In 10 -4 Under vacuum conditions, an Ag electrode with a thickness of 110 nm was deposited on the hole transport layer by thermal evaporation to obtain a perovskite solar cell.

[0071] Experimental Example 1 The photoelectric performance of the perovskite solar cells prepared in Examples 1-3, Comparative Examples 1 and 2 was tested using a solar photovoltaic simulator. The test results are shown in Table 1 below.

[0072] Table 1:

[0073] As shown in Table 1, the photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 1-3 is better than that of Comparative Examples 1 and 2. It can be seen that the present invention first prepares a thin, dense TiO2 barrier layer on a conductive substrate, which improves the photoelectric performance of the perovskite solar cells.

[0074] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms may refer to different embodiments or examples. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0075] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0076] Although embodiments of the invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims and their equivalents.

Claims

1. A method for preparing an electron transport layer with gradient porosity, characterized in that, Includes the following steps: (1) Tetrabutyl titanate solution was spin-coated onto a pretreated conductive substrate and sintered to obtain a dense TiO2 barrier layer; (2) Spin-coating the mesoporous TiO2 nanoparticle dispersion onto the dense TiO2 barrier layer and sintering to obtain a three-dimensional mesoporous layer; (3) The conductive substrate obtained in step (2) is placed in an acidic solution of tetrabutyl titanate and subjected to a hydrothermal reaction to obtain a one-dimensional TiO2 nanorod array grown on the three-dimensional mesoporous layer. (4) After taking out the conductive substrate obtained in step (3), rinse and sinter it to obtain an electron transport layer with gradient porosity.

2. The method as described in claim 1, characterized in that, The concentration of the tetrabutyl titanate solution is 0.2~0.4M.

3. The method as described in claim 1, characterized in that, In step (1), the spin coating speed is 3000~4000 rpm and the spin coating time is 30~50s; and / or, in step (1), the sintering temperature is 450~500℃ and the sintering time is 20~40min.

4. The method as described in claim 1, characterized in that, The thickness of the dense TiO2 barrier layer is 30~50nm; and / or, the thickness of the three-dimensional mesoporous layer is 100~200nm.

5. The method as described in claim 1, characterized in that, The mesoporous TiO2 nanoparticle dispersion is obtained by homogenizing mesoporous TiO2 nanoparticles in ethanol or terpineol.

6. The method as described in claim 1, characterized in that, The one-dimensional TiO2 nanorod array has nanorods with a diameter of 30-50 nm, a spacing of 90-120 nm, and a length of 400-700 nm.

7. The method as described in claim 1, characterized in that, The acidic solution of tetrabutyl titanate is obtained by first mixing hydrochloric acid and water evenly, and then adding tetrabutyl titanate dropwise while stirring until clear and transparent.

8. The method as described in claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 150-170℃ for 4-12 hours.

9. An electron transport layer with gradient porosity, characterized in that, Prepared by the method described in any one of claims 1 to 8.

10. A perovskite solar cell, characterized in that, Includes the electronic transport layer as described in claim 9.